2018
DOI: 10.1061/(asce)wr.1943-5452.0000996
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Multiobjective Optimization Methods Applied to Urban Drainage Adaptation Problems

Abstract: This article compares three multi-objective evolutionary algorithms (MOEAs) with application to the urban drainage system (UDS) adaptation of a capital city in North China.Particularly, the well-known NSGA-II, the built-in solver in the MATLAB Global Optimization Toolbox (MLOT), and a newly-developed hybrid MOEA called GALAXY are considered. A variety of parameter combinations of each MOEA are systemically applied to examine their impacts on optimization efficiency. Results suggest that traditional MOEAs suffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…The parameterization impact of NSGA-II is illustrated in the format of a compass plot initially used in [34]. Generally speaking, the compass plot is used to demonstrate how the performance of NSGA-II varies according to different combinations of its parameters.…”
Section: Proposed Methodology Of Investigating the Parameterization Omentioning
confidence: 99%
“…The parameterization impact of NSGA-II is illustrated in the format of a compass plot initially used in [34]. Generally speaking, the compass plot is used to demonstrate how the performance of NSGA-II varies according to different combinations of its parameters.…”
Section: Proposed Methodology Of Investigating the Parameterization Omentioning
confidence: 99%
“…The flood damage cost function represents damages caused by the flooding. Some authors consider flooding as a volume ( [34]); however, others present flooding as the highest depth reached by the water (y) out of the network. Lee and Kim [19] showed that flood damage is different from flood volume.…”
Section: Objective Functionsmentioning
confidence: 99%
“…In the literature, flooding is considered to be a volume for some authors [39] while other authors consider flooding as the highest depth reach by the water (y) out of the network. According to Lee and Kim [40], flooding damage is different from flooding volume.…”
Section: Flood Damage Cost Functionmentioning
confidence: 99%